Measuring the Maturity Level of Community Development and Empowerment Programs (PPM) in Coal Mining Companies - Giwa Giwangkara; Nunuk Andriastuti; Maria Ariestha Utha; Kurniawati Kurniawati (Journal of Social Research, 2023)
The coal industry is a relatively capital-intensive industry and has a relatively high level of social risk. In addition, the coal industry also has limited time because it depends on the amount of coal reserves. One of the social risk mitigations coal companies carry is conducting community development and empowerment programs (PPM). In measuring the level of maturity or independence of PPM programs, an approach is used by measuring scores from six dimensions, namely change, inclusive, organized, cooperation, influential, and sustainability. In this study, companies A and B differ in the maturity level of their flagship programs. The integrated farming program in Cattle Breeding A has the smallest level of maturity score of 5.76. While in Cattle Breeding B, the cattle breeding program has the smallest level of maturity value of 8.46.